Colfax County libraries benefitting from Legislature - funded internet grants. (Raton, New Mexico Raton Range, 1995)
In a project administered by the New Mexico State Library to make access to the internet widely available, the Raton High School Library and the Raton Middle School Library will provided with computers.
1 page article on Colfax County libraries getting internet grants.
Master list item # 99
File location is in the Raton File Cabinet drawer 3
Keywords: Raton High School -- Raton, New Mexico; Raton, New Mexico; Angel Fire, New Mexico; Eagle Nest, New Mexico